Evolution of the Phenolic Compounds Profile of Olive Leaf Extract Encapsulated by Spray-Drying During in Vitro Gastrointestinal Digestion - Gimenez-Castillo, B (Elsevier Ltd, 2019)
An olive leaf extract (OLE) was microencapsulated with sodium alginate (SA) by spray-drying to study the evolution of oleuropein (ORP) during in vitro gastrointestinal digestion, and its bioaccessibility and potential bioavailability from OLE and OLE-SA microparticles. Secoiridoids, flavonoids, simple phenols, oleosides and elenolic acid were identified in OLE. OLE/SA ratio 1:1.6 and inlet air temperature 135 °C were the optimal conditions for OLE-SA microparticles. ORP (70%) from OLE was degraded during gastric digestion, giving hydroxytyrosol and ORP-aglycone, whereas only the superficial ORP was released from microparticles. The remaining ORP from OLE was degraded under intestinal conditions, leading to oleosides; whereas alginate was swollen and disintegrated, releasing the ORP (90% of encapsulated ORP). ORP from both OLE and microparticles was degraded to hydroxytyrosol under colonic conditions. Encapsulation of OLE allowed the protection of ORP under gastric conditions and its controlled release at intestinal conditions, and higher bioaccessibility (58%) and potential bioavailability (20%). © 2018 Elsevier Ltd